Design of Information System for Outpatient Emergency Room Eligibility Letter to Support BPJS Claim Reporting - Jihan Fadillah; Yuda Syahidin; Erix Gunawan; Jeri Sukma Wijaya (Universitas Negeri Padang, 2023)
The advancement of technology in this era has had a significant impact on various fields, including healthcare. Hospitals strive to provide the best service to their patients so that they can get the best solution to their illnesses. A good hospital can be seen from the services provided to its patients. This research aims to produce an information system for creating patient eligibility letters in the emergency department. The method used in this research is a qualitative method with a descriptive approach by conducting data collection stages through interviews, observations, and literature studies, and the method used for developing the device is the System Development Life Cycle (SDLC) method. From this research, several problems were found in processing the creation of patient eligibility letters, namely the creation of eligibility letters still uses claim that has not been bridged with sims, causing the process of creating patient eligibility letters to take a long time, thus affecting the quality of healthcare services in the hospital's emergency unit. The suggestion given is the need for a redesign in the sims system to be bridged with vclaim.